Evidence of duplicated Hox genes in the most recent common ancestor of extant scorpions. Issue 6 (23rd October 2015) - Sharma, Prashant P.; Santiago, Marc A.; González‐Santillán, Edmundo; Monod, Lionel; Wheeler, Ward C.
SUMMARY Scorpions (order Scorpiones) are unusual among arthropods, both for the extreme heteronomy of their bauplan and for the high gene family turnover exhibited in their genomes. These phenomena appear to be correlated, as two scorpion species have been shown to possess nearly twice the number of Hox genes present in most arthropods. Segmentally offset anterior expression boundaries of a subset of Hox paralogs have been shown to correspond to transitions in segmental identities in the scorpion posterior tagmata, suggesting that posterior heteronomy in scorpions may have been achieved by neofunctionalization of Hox paralogs. However, both the first scorpion genome sequenced and the developmental genetic data are based on exemplars of Buthidae, one of 19 families of scorpions. It is therefore not known whether Hox paralogy is limited to Buthidae or widespread among scorpions. We surveyed 24 high throughput transcriptomes and the single whole genome available for scorpions, in order to test the prediction that Hox gene duplications are common to the order. We used gene tree parsimony to infer whether the paralogy was consistent with a duplication event in the scorpion common ancestor. Here we show that duplicated Hox genes in non‐buthid scorpions occur in six of the ten Hox classes. Gene tree topologies and parsimony‐based reconciliation of the gene trees are consistent with a duplication event in the most recent common ancestor of scorpions. These results suggest that a Hox paralogy, and by extension the model of posterior patterning established in a buthid, can be extended to non‐Buthidae scorpions.